Intervention to Enhance Reading Comprehension Skills of Grade 7 Students through Background Knowledge Activation, Repeated Readings, Reading Aloud, and Asking Questions - Caabay, Ma. Thessa; Martinez , Louela; Valdestamon, Jenny; Aguhayon, Hernalyn (International Journal of Education and Teaching Zone, 2024)
This study sought to assess the reading proficiency of 23 purposively selected seventh-grade students at Caponayan National High School during the academic year 2023-2024, focusing on their reading comprehension levels. These assessments were the foundation for developing an effective reading program tailored to students’ needs. Over four weeks, data collection involved repeated reading-aloud sessions and immediate questioning post-reading. In the educational process carried out in the Philippines, the Informal Reading Inventory standard is used. The analysis revealed that the respondents demonstrated mastery of essential sight words, with only a few identified miscues. Significantly, the number of students experiencing frustration decreased from 16 to 4 after the intervention, accompanied by notable improvements in reading comprehension. The instructional level increased from 7 to 13, while the highest comprehension level, classified as independent, rose from 0 to 6. Assessing the students’ overall performance before and after the intervention indicated substantial progress. Statistical analysis demonstrated a significant difference before and after the intervention. Based on these findings, the study concludes that even a brief intervention can significantly improve students’ reading abilities.